Saving soil carbon, greenhouse gas emissions, biodiversity and the economy: paludiculture as sustainable land use option in German fen peatlands - Franziska Tanneberger; Friedrich Birr; John Couwenberg; Moritz Kaiser; Vera Luthardt; Monique Nerger; Sonja Pfister; Rainer Oppermann; Jutta Zeitz; Colja Beyer; Sebastian van der Linden; Wendelin Wichtmann; et al. (Regional Environmental Change, 2022)
Peatlands in the European Union are largely drained for agriculture and emit 25% of the total agricultural greenhouse gas emissions. Drainage-based peatland use has also negative impacts on water quality, drinking water provision and biodiversity. Consequently, key EU environmental policy objectives include the rewetting of all drained peatlands as an essential nature-based solution. Rewetting of peatlands can be combined with site-adapted land use, so-called paludiculture. Paludiculture produces biomass from wet and rewetted peatlands under conditions that maintain the peat body, facilitate peat accumulation and can provide many of the ecosystem services associated with natural, undrained peatlands. The biomass can be used for a wide range of traditional and innovative food, feed, fibre and fuel products. Based on examples in Germany, we have analysed emerging paludiculture options for temperate Europe with respect to greenhouse gas fluxes, biodiversity and indicative business economics. Best estimates of site emission factors vary between 0 and 8 t CO 2 eq ha −1 y −1 . Suitability maps for four peatland-rich federal states (76% of total German peatland area) indicate that most of the drained, agriculturally used peatland area could be used for paludiculture, about one-third of the fen area for any paludiculture type. Fen-specific biodiversity benefits from rewetting and paludiculture, if compared to the drained state. Under favourable conditions, paludiculture can be economically viable, but costs and revenues vary considerably. Key recommendations for large-scale implementation are providing planning security by paludiculture spatial planning, establishing best practice sites and strengthening research into crops, water tables and management options.

Organic Agriculture 3.0 is innovation with research - Gerold Rahmann; M. Reza Ardakani; Paolo Bàrberi; Herwart Boehm; Stefano Canali; Mahesh Chander; Wahyudi David; Lucas Dengel; Jan Willem Erisman; Ana C. Galvis-Martinez; Ulrich Hamm; Johannes Kahl; et al. (Organic Agriculture, 2017)